Special Education is Required for Individuals Pursuing A Career as An Advocate, As Stated In Article 3, Paragraph (1), Letter F of The Republic of Indonesia Law Number 18 of 2003, Which Pertains to Advocates. - Subrata, Tedy (Jurnal Legisci, 2024)
Special Education for the Advocate Profession (PKPA) is a requirement stipulated by the State Law of the Republic of Indonesia Number 18 of 2003 regarding Advocates. Special Education for the Advocate Profession is a mandatory program designed for those with a bachelor's degree and a foundation in law education. The socializing event had 30 prospective advocates and occurred on October 14, 2023, at the University of Tangerang Raya Tiga Raksa in Tangerang Regency. The Service Learning (SL) method aims to incorporate learning into the Special Education of the Advocate Profession (PKPA) or the collaboration between the National Leadership Council of the Indonesian Advocates Association (DPN PERSADIN) and the Faculty of Law, University of Tangerang Raya (UNTARA). Furthermore, the Participatory Action Research (PAR) methodology emphasizes explicitly the empowerment of individuals involved in the Special Education for the Advocate Profession (PKPA). This arises from the necessity to address legal issues inside the community. Volunteers from higher education institutions should prioritize the community as the primary agent of development and transformation. This activity aims to establish and promote advocacy, emphasizing that advocates are esteemed professionals who possess freedom, independence, and responsibility in upholding the law. The activities of this profession are legally safeguarded and protected to ensure the implementation of the Rule of Law.